2016
DOI: 10.1002/ana.24682
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long‐term disability accrual in relapse‐onset multiple sclerosis

Abstract: We provide evidence of long-term treatment benefit in a large registry cohort, and provide evidence of long-term protective effects of pregnancy against disability accrual. We demonstrate that high annualized relapse rate, particularly on-treatment relapse, is an indicator of poor prognosis. Ann Neurol 2016;80:89-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 45 publications
14
155
0
3
Order By: Relevance
“…13 One explanation for this difference could be sample size. 13 One explanation for this difference could be sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 One explanation for this difference could be sample size. 13 One explanation for this difference could be sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies found no substantial impact of relapses on long-term disability progression in participants who had reached specific MS milestones. 13 The generally accepted model of MS disability proposes a 2-stage process in which poor recovery from relapses underlies disability progression during the relapsing phase of MS, which is followed by insidious decline in function caused by neurodegeneration in the secondary progressive disease phase. [8][9][10][11][12] A recent study using the large MSBase dataset found that relapses contribute, at least in part, to long-term disability.…”
mentioning
confidence: 99%
“…Long-term treatment effectiveness in patients with MS in a daily clinical setting has only been sparsely studied. Some observational studies have compared patients with MS treated with DMT with untreated patients with MS [8][9][10][11][12], whereas only a few studies have evaluated the effect of early treatment start on disability progression [13][14][15][16]. In contrast to well-conducted RCTs, observational and extension studies are more susceptible to confounding and bias [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…relapses), and to reduce or, ideally, to prevent long term disability accrual [36]. However, few studies have been conducted in the long term and, apparently, the use of DMTs might be responsible for delaying the reaching of milestones of disability progression [4,7]. Notwithstanding this, DMTs are nowadays the main responsible for direct healthcare costs in MS, and are expected to have a further expansion among overall expenses as a consequence of the introduction of newer and more effective drugs characterized by high healthcare costs for administration and management [811].…”
Section: Introductionmentioning
confidence: 99%